The Effect of Mental Training in Learning the Skill of the Human Wheel in Artistic Gymnastics for Girls (International Journal of Psychosocial Rehabilitation, 2020)
Mental training is important in the process of control and control of ideas and physical movements and the organization of motor behavior for the purpose of gaining the development of the level of motor skills and development and expecting better performance; therefore, the importance of research is to identify the impact of mental training in learning the skill of the human wheel in the game of artistic gymnastics for girls. This research aims to identify the effect of mental training in learning the skill of the human wheel in the game of artistic gymnastics for girls for second-grade students in the Faculty of Physical Education and Sports Science at the University of Baghdad. The researcher concluded that the improvement of motor performance as the skill progresses through repetitions and gradually, where the impact of mental training begins in the late stages of accurate compatibility and continues with the mechanical compatibility, and that mental training helps to increase the proportion of students who reach the stage of automatic performance.